Mismatches and criminal justice policy: The case of GPS for domestic violence - Ibarra, Peter R. (Criminology & criminal justice, 2024)
Mismatches are incongruencies between programmatic policies and working practices that engender counter-productive dynamics or outcomes relative to aspirations. The present article addresses electronic monitoring programs for domestic violence/intimate partner violence, examining how mismatches may emerge during their implementation or later. Electronic monitoring programs aim to surveil and deter defendants facing domestic violence/intimate partner violence–related charges during court-supervised release, with the aim of enhancing victim safety. Analysis of qualitative and survey data from a national (US) study suggests that domestic violence/intimate partner violence–focused strategies reliant on surveillance technology may be prone to generating mismatches rooted in discrepancies between victims’ expectations, defendant risk profiles, and program operations. Policy implications of mismatches in victim-focused initiatives are considered.